Synemin Redefined: Multiple Binding Partners Results in Multifunctionality - Russell, Mary A. (Frontiers in Cell and Developmental Biology, 2020)
Historically synemin has been studied as an intermediate filament protein. However, synemin also binds the type II regulatory (R) subunit alpha of protein kinase A (PKA) and protein phosphatase type 2A, thus participating in the PKA and phosphoinositide 3-kinase (PI3K)-Akt and signaling pathways. In addition, recent studies using transgenic mice indicate that a significant function of synemin is its role in signaling pathways in various tissues, including the heart. Recent clinical reports have shown that synemin mutations led to multiple cases of dilated cardiomyopathy. Additionally, a single case of the rare condition ulnar-mammary-like syndrome with left ventricular tachycardia due to a mutation in the synemin gene (SYNM) has been reported. Therefore, this review uses these recent studies to provide a new framework for detailed discussions on synemin tissue distribution, binding partners and synemin in disease. Differences between alpha- and beta-synemin are highlighted. The studies presented here indicate that synemin is not just an intermediate filament protein, but also a regulator of signaling pathways and a crosslinker. Also evident is that the dominant function(s) are isoform-, developmental-, and tissue-specific.